2009
DOI: 10.4337/9781848447240
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Routines

Abstract: Organizational routines and capabilities have become key constructs not only in evolutionary economics, but more recently also in business administration, specifically strategic management. In this chapter we explicate some of the underlying theoretical problems of these concepts, and discuss the need for micro-foundations. Specifically, we focus on some of the explanatory problems of collective-level theorizing, and what we think are tenuous assumptions about human beings. We argue that individual-level consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A complementary line of work in strategy explores the general origins of capabilities or dynamic capabilities (e.g., Helfat and Lieberman, 2002;Klepper, 2002;Pisano, 2000;Zollo and Winter, 2002). Building on this work, several recent theoretical and empirical studies devote explicit attention to the micro-level origins of routines and capabilities (Becker and Lazaric, 2003;Becker et al, 2005;D'Addiero, 2009;Gavetti, 2005;Heimeriks, Schijven, and Gates, in press;Helfat and Peteraf, 2010;Salvato, 2009;Rerup and Feldman, 2011;Pentland, 2003, Pentland andFeldman 2008;Teece, 2007). Thus, situated at the nexus of this extant and emerging work, the goal of this paper (and the associated Special Issue) is to clarify, and expand on, the microfoundations lens and define a research agenda for further work on the microfoundations of routines and capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…A complementary line of work in strategy explores the general origins of capabilities or dynamic capabilities (e.g., Helfat and Lieberman, 2002;Klepper, 2002;Pisano, 2000;Zollo and Winter, 2002). Building on this work, several recent theoretical and empirical studies devote explicit attention to the micro-level origins of routines and capabilities (Becker and Lazaric, 2003;Becker et al, 2005;D'Addiero, 2009;Gavetti, 2005;Heimeriks, Schijven, and Gates, in press;Helfat and Peteraf, 2010;Salvato, 2009;Rerup and Feldman, 2011;Pentland, 2003, Pentland andFeldman 2008;Teece, 2007). Thus, situated at the nexus of this extant and emerging work, the goal of this paper (and the associated Special Issue) is to clarify, and expand on, the microfoundations lens and define a research agenda for further work on the microfoundations of routines and capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, routines were primarily considered as encapsulating inertia (Hannan and Freeman, 1984), mindlessness (Ashforth and Fried, 1988), demotivation (Ilgen and Hollenbeck, 1991), competency traps (March, 1991) or stability and repetition (Cohen et al, 1996;Gersick and Hackman, 1990). However, more recent studies have shown that routines also represent a source of organizational change and flexibility as human actors are involved in carrying out routines and have capabilities to adjust them to their interests (Becker and Lazaric, 2003;Becker et al, 2005;Feldman, 2000;Feldman and Pentland, 2003;Rerup and Feldman, 2011).…”
Section: Management Accounting Routines In Routine Clustersmentioning
confidence: 99%